(3acQI GdMeGjI GdLfGFjI dHQGeL GdMGSH GdBdj (B/s - (3TJG, eMeO eMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3HQGeL GdMGSH GdBdj Hjf GdMeGjI GdeOfjI hGdMeGjI GdLfGFjI(B- (3eGgjI HQGeL GdMGSH GdBdj GdJj jJe MeGjJgG(B- (3NUGFU LQjeI GdEYJOGA Ydi HQGeL GdMGSH GdBdj(B- (3UYhHI GKHGJ LQjeI GdEYJOGA Ydi HQGeL GdMGSH GdBdjs
(3GdeQGLY U(B.137s
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGfhf GdLfGFj (B- (3HQGeL GdMGSHGJs